Anti-cmas composite thermal barrier coating and method of making same
Patent Information
- Application Number
- CN202611175543.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-27
AI Technical Summary
这些颗粒在燃烧室内的高温环境下熔化为液态CMAS熔体,并随高速高压燃气流冲击涡轮叶片表面,造成热障涂层剥落与失效,严重危及发动机的可靠性与安全运行
[0036](1)制备抗CMAS复合结构时,通过飞秒激光加工在陶瓷层表面构建的类荷叶结构,能够有效调控陶瓷层表面熔融CMAS的润湿行为,降低CMAS浸润与铺展,同时激光加工形成的微纳凹凸结构为后续膜层提供有利于结合的界面,改善氧化镁膜层与陶瓷层的结合稳定性。
Smart Images

Figure CN122977845A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of thermal barrier coating corrosion and protection technology, and in particular to anti-CMAS composite thermal barrier coatings and their preparation methods. Background Technology
[0002] As aero-engines develop towards higher efficiency and higher thrust-to-weight ratios, turbine inlet temperatures are continuously increasing, placing higher demands on the high-temperature resistance of turbine blades. Currently, aero-engine turbine blades are typically made of nickel-based superalloys. While these materials possess good high-temperature strength and oxidation resistance, their long-term service temperature is still limited by the material's inherent heat resistance, making it difficult to meet the high-temperature service requirements of advanced aero-engines. Therefore, thermal barrier coating technology is needed to provide thermal protection to the superalloy substrate to improve the blade's temperature resistance and service life.
[0003] Thermal barrier coating is a thermal protection technology that deposits ceramic materials with low thermal conductivity, high temperature resistance, and corrosion resistance onto the surface of a high-temperature alloy substrate in the form of a coating. By reducing heat transfer to the substrate, it increases the service temperature of engine blades while enhancing their oxidation and corrosion resistance, thereby improving engine thrust, fuel efficiency, and service life.
[0004] However, during actual service, aero engines often ingest calcium magnesium aluminum silicate (CaO-MgO-Al2O3-SiO2, or CMAS) particles from environments such as desert sand and atmospheric dust. These particles melt into liquid CMAS melt in the high-temperature environment of the combustion chamber and impact the turbine blade surface with the high-speed, high-pressure gas flow, causing the thermal barrier coating to peel off and fail, seriously endangering the reliability and safe operation of the engine. Summary of the Invention
[0005] Based on this, this application provides a CMAS-resistant composite thermal barrier coating and its preparation method to improve the corrosion of the thermal barrier coating by environmental deposits CMAS.
[0006] A first aspect of this application provides a thermal barrier coating with an anti-CMAS composite structure, comprising an anti-CMAS composite structure, the anti-CMAS composite structure including:
[0007] A ceramic layer, wherein the material of the ceramic layer comprises at least one of gadolinium zirconate and rare-earth modified gadolinium zirconate, and the surface of the ceramic layer has a lotus leaf-like structure; and,
[0008] A magnesium oxide film layer covers the lotus leaf-like structure surface of the ceramic layer.
[0009] In some embodiments, the height of the lotus leaf-like structure is 7μm-12μm.
[0010] In some embodiments, the half-width at half-maximum (WHM) of the lotus-like structure is 4 μm-6 μm.
[0011] In some embodiments, the surface of the ceramic layer has the lotus leaf-like structure, which is arranged in an array.
[0012] In some embodiments, the distance between the tips of adjacent lotus-like structures is 9 μm-11 μm.
[0013] In some embodiments, the thickness of the magnesium oxide film is 1 μm-4 μm.
[0014] In some embodiments, the thickness of the ceramic layer is 100μm-400μm.
[0015] In some embodiments, the thickness of the ceramic layer is 100μm-300μm.
[0016] In some embodiments, the rare earth-modified gadolinium zirconate is ytterbium-modified gadolinium zirconate.
[0017] In some embodiments, the rare-earth-modified gadolinium zirconate is ytterbium-modified gadolinium zirconate, and the chemical formula of the ytterbium-modified gadolinium zirconate is (Gd 0.9 Yb 0.1 )2Zr2O7.
[0018] In some embodiments, the anti-CMAS composite thermal barrier coating further includes an adhesive layer, wherein the adhesive layer and the anti-CMAS composite structure are stacked sequentially.
[0019] In some embodiments, the thickness of the adhesive layer is 40 μm-70 μm.
[0020] A second aspect of this application provides a method for preparing a CMAS-resistant composite thermal barrier coating, wherein the CMAS-resistant composite thermal barrier coating comprises an CMAS-resistant composite structure, and the preparation method includes the step of preparing the CMAS-resistant composite structure, the step of preparing the CMAS-resistant composite structure comprising:
[0021] The surface of the ceramic layer is processed by femtosecond laser to form a lotus leaf-like micro / nano structure on the surface of the ceramic layer; wherein the material of the ceramic layer includes at least one of gadolinium zirconate and rare earth modified gadolinium zirconate;
[0022] Magnesium oxide was used as the target material to perform magnetron sputtering deposition on the surface of a ceramic layer with a lotus leaf-like micro-nano structure, forming a magnesium oxide film on the surface of the lotus leaf-like micro-nano structure of the ceramic layer, thus obtaining an anti-CMAS composite structure.
[0023] In some embodiments, the center wavelength of the laser used in femtosecond laser processing is 343 nm.
[0024] In some embodiments, the average power of femtosecond laser processing is 1W-20W.
[0025] In some embodiments, the scanning speed of the femtosecond laser processing is 10 mm / s-1000 mm / s.
[0026] In some embodiments, the femtosecond laser treatment is repeated 1 to 20 times.
[0027] In some embodiments, the vacuum level in the main process chamber during magnetron sputtering deposition is 5 × 10⁻⁶. -6 Torr.
[0028] In some embodiments, the argon flow rate during magnetron sputtering deposition is 50 sccm-100 sccm.
[0029] In some embodiments, the target gun power during magnetron sputtering deposition is 50W-150W.
[0030] In some embodiments, the ambient temperature during magnetron sputtering deposition is 100°C-300°C.
[0031] In some embodiments, the magnetron sputtering deposition time is 2 hours to 10 hours.
[0032] In some embodiments, the rare earth-modified gadolinium zirconate is ytterbium-modified gadolinium zirconate.
[0033] In some embodiments, the rare-earth-modified gadolinium zirconate is ytterbium-modified gadolinium zirconate, and the chemical formula of the ytterbium-modified gadolinium zirconate is (Gd 0.9 Yb 0.1 )2Zr2O7.
[0034] In the aforementioned anti-CMAS composite thermal barrier coating, the lotus leaf-like structure on the ceramic layer surface can initially regulate the wettability of the ceramic layer surface, slowing down the wetting and spreading of molten CMAS on its surface, while also improving the bonding strength between the magnesium oxide film layer and the substrate. The magnesium oxide film layer, as a physical protective barrier, can effectively inhibit its corrosion penetration into the ceramic layer. The synergistic protection of the lotus leaf-like structure and the magnesium oxide film layer compensates for the limited capabilities of individual protection methods, thereby improving the thermal barrier coating's resistance to CMAS erosion, high-temperature stability, and service life.
[0035] The above-described method for preparing the anti-CMAS composite thermal barrier coating has at least the following beneficial effects:
[0036] (1) When preparing the anti-CMAS composite structure, the lotus leaf-like structure constructed on the surface of the ceramic layer by femtosecond laser processing can effectively control the wetting behavior of molten CMAS on the surface of the ceramic layer, reduce CMAS wetting and spreading, and at the same time, the micro-nano uneven structure formed by laser processing provides an interface that is conducive to the bonding of subsequent film layers, improving the bonding stability between the magnesium oxide film layer and the ceramic layer.
[0037] (2) When preparing the anti-CMAS composite structure, a magnesium oxide film is deposited on the surface of the ceramic layer processed by femtosecond laser. The excellent high-temperature stability of magnesium oxide is used as an external protective barrier to effectively reduce the erosion of the ceramic layer by CMAS. Magnesium oxide has high compatibility with magnetron sputtering process and can be deposited on the lotus leaf-like structure modified by femtosecond laser to form a continuous film layer.
[0038] (3) When preparing the anti-CMAS composite structure, the lotus leaf-like structure formed by femtosecond laser processing increases the surface roughness of the substrate, which can improve the adhesion stability of the magnesium oxide film. The lotus leaf-like structure and the magnesium oxide film work synergistically to achieve multiple long-term protective effects of "physical barrier (film) + interface strengthening (laser modification) + potential chemical barrier (reaction layer)". The lotus leaf-like structure and the magnesium oxide film form a synergistic protective effect, which overcomes the problem of limited protection capability of single protection methods in the CMAS erosion environment, thereby improving the CMAS erosion resistance and high-temperature service stability of the thermal barrier coating and extending its service life.
[0039] (4) When preparing the anti-CMAS composite structure, femtosecond laser was selected as the surface structure modification method. Compared with conventional laser processing methods such as nanosecond laser and picosecond laser, its advantage lies in the fact that the laser pulse duration reaches the femtosecond level (10^6 seconds) during the processing. -15 With a processing time of only 1.5 seconds, the thermal diffusion time during processing is extremely short, which can significantly reduce the heat-affected zone and avoid significant thermal damage, remelting, and crack propagation in ceramic materials. In addition, the processing precision of femtosecond lasers is far higher than that of conventional lasers, enabling precise micro-nano-level engraving, thereby obtaining lotus leaf-like structures with controllable morphology and good repeatability, providing favorable conditions for uniform deposition of magnesium oxide films and improved interfacial bonding performance. Attached Figure Description
[0040] To more clearly illustrate the technical solutions in the embodiments of this application and to more completely understand this application and its beneficial effects, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0041] Figure 1 A cross-sectional schematic diagram of an anti-CMAS composite structure provided in one embodiment.
[0042] Figure 2 The (Gd) obtained after S3 laser processing in Example 1 0.9 Yb 0.1 Three-dimensional laser confocal topography of the lotus leaf-like structure on the surface of the Zr2O7 ceramic layer.
[0043] Figure 3 The images show the cross-sectional SEM image and EDS elemental distribution diagram of the anti-CMAS composite structure prepared in Example 1.
[0044] Figure 4 The images show SEM images of the corrosion results from the CMAS corrosion experiments of Example 1 and Comparative Example 1.
[0045] Figure 5 The figures show the contact angle test results for Example 1 and Comparative Example 1. Detailed Implementation
[0046] To facilitate understanding of the present invention, a more complete description of this application will be provided below with reference to relevant embodiments. Preferred embodiments of the present application are given below. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided so that a thorough and complete understanding of the disclosure of this application will be achieved.
[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.
[0048] As used herein, the terms "and / or," "or / and," and "and / or" encompass any one of two or more of the related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. It should be noted that when at least three items are connected using at least two conjunctions selected from "and / or," "or / and," and "and / or," it should be understood that, in this application, the technical solution undoubtedly includes solutions connected by "logical AND," and also undoubtedly includes solutions connected by "logical OR."
[0049] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0050] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0051] This document only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form an unspecified range.
[0052] Unless otherwise specified, the temperature parameters in this application may be either constant temperature processing or processing within a certain temperature range. The constant temperature processing allows temperature fluctuations within the precision range controlled by the instrument, such as ±5°C, ±4°C, ±3°C, ±2°C, or ±1°C.
[0053] In this application, unless otherwise specified, the terms "size," "particle size," and "diameter" generally refer to average values. In this application, "particle size" and "particle diameter" have the same definition, both representing the average particle size of spheres or spheroids.
[0054] In this document, the term "suitable" as used in phrases such as "suitable combination," "suitable method," and "any suitable method" refers to the ability to implement the technical solution of this application, solve the technical problem of this application, and achieve the expected technical effect of this application.
[0055] In this application, terms such as "further," "even further," and "particularly" are used to describe purposes and indicate differences in content, but should not be construed as limiting the scope of protection of this application.
[0056] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it means that it is selected from either "with" or "without." If there are multiple "optional" entries in a technical solution, unless otherwise specified, and there are no contradictions or mutual constraints, each "optional" entry shall be independent.
[0057] In the description of the application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0058] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions. Unless otherwise specified, all technical features and optional technical features of this application can be combined to form new technical solutions.
[0059] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, but sequentially is preferred.
[0060] During actual operation, aero engines often ingest calcium magnesium aluminum silicate (CMAS) particles from environments such as desert sand and atmospheric dust. These particles melt into liquid CMAS in the high-temperature environment of the combustion chamber, and are then impacted on the turbine blade surface by the high-speed, high-pressure gas flow. The molten CMAS can cause thermal barrier coating peeling and failure through various means, including blocking cooling pores, penetrating through the pores inside the thermal barrier coating, reacting chemically with the coating material to form low-melting-point products, and generating stress during solidification that leads to coating cracking. This seriously endangers the reliability and safe operation of the engine.
[0061] Research on the corrosion protection performance of thermal barrier coatings in related technologies mainly falls into two categories:
[0062] One type of method involves modifying the material composition of the ceramic layer. This method alters the composition of the ceramic layer by introducing elements with CMAS reactivity, causing them to react with the CMAS melt and generate high-melting-point reaction products. This increases the melt viscosity and reduces the CMAS penetration rate. While this method can alleviate CMAS corrosion to some extent, adjusting the material composition typically affects the thermal conductivity, coefficient of thermal expansion, and phase stability of the ceramic layer. It cannot simultaneously address both thermophysical properties and protective effects, and can easily lead to a decrease in the thermal compatibility between the coating and the substrate.
[0063] Another type is surface structure modification, which modifies the wetting behavior of CMAS by constructing micro- and nano-structures on the material surface. However, such micro- and nano-structures are prone to sintering, creep, or oxidation at high temperatures (>1200℃), resulting in rapid morphological degradation. Furthermore, they are difficult to adapt to complex curved workpieces and cannot maintain long-term impermeability.
[0064] Based on the above problems, this application proposes a composite thermal barrier coating that combines surface structure regulation with an oxide protective layer to resist CMAS. Through the synergistic effect of the lotus leaf-like structure on the ceramic layer surface and the magnesium oxide film layer, a composite protection mechanism combining interface strengthening and physical barrier is achieved, thereby improving the CMAS corrosion resistance and long-term service reliability of the thermal barrier coating.
[0065] The first aspect of this application provides a thermal barrier coating for an anti-CMAS composite structure, including an anti-CMAS composite structure comprising a ceramic layer and a magnesium oxide film layer. The ceramic layer is made of at least one of gadolinium zirconate and rare earth modified gadolinium zirconate. The surface of the ceramic layer has a lotus leaf-like structure, and the magnesium oxide film layer covers the lotus leaf-like structure surface of the ceramic layer.
[0066] It should be noted that the lotus leaf-like structure mentioned in the context refers to a regularly arranged micron-sized conical protrusion structure formed on the surface of the ceramic layer after laser processing. It presents a biomimetic structure similar to a lotus leaf and has excellent resistance to molten CMAS wetting. This allows the molten CMAS to have a large contact angle on its surface, reducing interfacial adhesion and the spread of molten CMAS on the coating surface. This is beneficial for the CMAS to be peeled off by centrifugal force and airflow under actual high-speed blade rotation conditions, thus weakening the degree of CMAS erosion of the thermal barrier coating.
[0067] Understandably, in the CMAS-resistant composite thermal barrier coating of this application, the lotus leaf-like structure on the ceramic layer surface can initially regulate the wettability of the ceramic layer surface, reducing the wetting and spreading of molten CMAS on its surface, while also improving the bonding strength between the magnesium oxide film layer and the substrate. The magnesium oxide film layer, as a physical protective barrier, can inhibit its corrosion penetration into the ceramic layer. The lotus leaf-like structure and the magnesium oxide film layer form a synergistic protective effect, overcoming the limited protective capability of single protective methods in CMAS erosion environments, thereby improving the CMAS erosion resistance, high-temperature service stability, and extending the service life of the thermal barrier coating.
[0068] As an example, a cross-sectional schematic diagram of the anti-CMAS composite structure is shown below. Figure 1 As shown, by Figure 1 It can be seen that the anti-CMAS composite structure includes a ceramic layer 1 and a magnesium oxide film layer 2. The material of the ceramic layer 1 is ytterbium-modified gadolinium zirconate (GYbZ, (Gd 0.9 Yb 0.1 The ceramic layer 1 (2Zr2O7) has a lotus leaf-like structure 12 on its surface, and a magnesium oxide film layer 2 covers the surface of the ceramic layer 1 with the lotus leaf-like structure 12. The magnesium oxide film layer 2 can slow down the penetration of CMAS melt 3.
[0069] In some embodiments, the height of the lotus leaf-like structure is 7μm-12μm; for example, it can be, but is not limited to, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm or any range between the two of the above heights.
[0070] It should be noted that the height of the lotus leaf-like structure mentioned in the context refers to the vertical distance from the bottom to the top of the lotus leaf-like structure in the direction perpendicular to the surface of the ceramic layer with the lotus leaf-like structure.
[0071] As one possible implementation, the half-width at half-maximum (WHM) of the lotus leaf-like structure is 4μm-6μm; for example, it can be, but is not limited to, 4μm, 4.2μm, 4.4μm, 4.6μm, 4.8μm, 5μm, 5.2μm, 5.4μm, 5.6μm, 5.8μm, 6μm, or any range between the two heights mentioned above.
[0072] It should be noted that the half-width of the lotus leaf-like structure mentioned in the context refers to the width at half the height of the lotus leaf-like structure.
[0073] When the height and half-width at half-maximum of the lotus leaf-like structure are within the above ranges, it is beneficial to construct stable low-wetting micro / nano structures.
[0074] In some embodiments, the surface of the ceramic layer has a lotus leaf-like structure arranged in an array. This allows for the control of the wettability of the ceramic layer surface, increasing the contact angle between the CMAS and the ceramic layer, thereby reducing the contact area of the molten CMAS on the ceramic layer surface.
[0075] In some optional embodiments, the distance between the tips of adjacent lotus leaf-like structures is 9μm-11μm. For example, it can be, but is not limited to, 9μm, 9.2μm, 9.4μm, 9.6μm, 9.8μm, 10μm, 10.2μm, 10.4μm, 10.6μm, 10.8μm, 11μm, or any range between two of the above distances. This is beneficial for increasing the contact angle between the CMAS and the ceramic layer.
[0076] As one possible implementation, the thickness of the magnesium oxide film is 1 μm-4 μm; for example, it can be, but is not limited to, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4 μm, or any range between two of the above distances. This reduces the corrosion depth of the CMAS.
[0077] In some embodiments, the thickness of the ceramic layer is 100 μm-400 μm. For example, it can be, but is not limited to, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, or any range between two of the above thicknesses. In some optional embodiments, the thickness of the ceramic layer is 100 μm-300 μm.
[0078] In some embodiments, the rare earth-modified gadolinium zirconate is ytterbium-modified gadolinium zirconate.
[0079] As one possible implementation method, the rare-earth modified gadolinium zirconate is ytterbium-modified gadolinium zirconate, and the chemical formula of ytterbium-modified gadolinium zirconate is (Gd 0.9 Yb 0.1 )2Zr2O7.
[0080] In some embodiments, the anti-CMAS composite thermal barrier coating further includes an adhesive layer, and the adhesive layer and the anti-CMAS composite structure are stacked sequentially.
[0081] As one possible implementation, the thickness of the adhesive layer is 40μm-70μm; for example, it can be, but is not limited to, 40μm, 50μm, 60μm, 70μm or any range between the two of the above thicknesses.
[0082] A second aspect of this application provides a method for preparing an anti-CMAS composite thermal barrier coating, used to prepare the aforementioned anti-CMAS composite thermal barrier coating. The anti-CMAS composite thermal barrier coating includes an anti-CMAS composite structure. The method for preparing the anti-CMAS composite structure includes: performing femtosecond laser processing on the surface of a ceramic layer to form a lotus leaf-like micro / nano structure on the surface of the ceramic layer; wherein the material of the ceramic layer includes at least one of gadolinium zirconate and rare-earth-doped modified gadolinium zirconate; using magnesium oxide as a target, performing magnetron sputtering deposition on the surface of the ceramic layer with the lotus leaf-like micro / nano structure to form a magnesium oxide film layer on the surface of the lotus leaf-like micro / nano structure of the ceramic layer, thereby obtaining the anti-CMAS composite structure.
[0083] Understandably, the method for preparing the CMAS-resistant composite thermal barrier coating of this application has at least the following beneficial effects:
[0084] (1) When preparing the anti-CMAS composite structure, the lotus leaf-like structure constructed on the surface of the ceramic layer by femtosecond laser processing can effectively control the wetting behavior of molten CMAS on the surface of the ceramic layer, reduce CMAS wetting and spreading, and at the same time, the micro-nano uneven structure formed by laser processing provides an interface that is conducive to the bonding of subsequent film layers, improving the bonding stability between the magnesium oxide film layer and the ceramic layer.
[0085] (2) When preparing the anti-CMAS composite structure, a magnesium oxide film is deposited on the surface of the ceramic layer processed by femtosecond laser. The excellent high-temperature stability of magnesium oxide is utilized to make it an external protective barrier, effectively reducing the erosion of the ceramic layer by the CMAS melt. Magnesium oxide has high compatibility with magnetron sputtering process and can be deposited on the lotus leaf-like structure modified by femtosecond laser to form a continuous film layer.
[0086] (3) When preparing the anti-CMAS composite structure, the lotus leaf-like structure formed by femtosecond laser processing increases the surface roughness of the substrate, which can improve the adhesion stability of the magnesium oxide film. The lotus leaf-like structure and the magnesium oxide film work synergistically to achieve multiple long-term protective effects of "physical barrier (film) + interface strengthening (laser modification) + potential chemical barrier (reaction layer)". The lotus leaf-like structure and the magnesium oxide film form a synergistic protective effect, which overcomes the problem of limited protection capability of single protection methods in the CMAS erosion environment, thereby improving the CMAS erosion resistance and high-temperature service stability of the thermal barrier coating and extending its service life.
[0087] (4) When preparing the anti-CMAS composite structure, femtosecond laser was selected as the surface structure modification method. Compared with conventional laser processing methods such as nanosecond laser and picosecond laser, its advantage lies in the fact that the laser pulse duration reaches the femtosecond level (10^6 seconds) during the processing. -15 With a processing time of only 1.5 seconds, the thermal diffusion time during processing is extremely short, which can significantly reduce the heat-affected zone and avoid significant thermal damage, remelting, and crack propagation in ceramic materials. In addition, the processing precision of femtosecond lasers is far higher than that of conventional lasers, enabling precise micro-nano-level engraving, thereby obtaining lotus leaf-like structures with controllable morphology and good repeatability, providing favorable conditions for uniform deposition of magnesium oxide films and improved interfacial bonding performance.
[0088] It should be noted that the anti-CMAS composite structure prepared by this method has similar technical solutions and beneficial effects to the anti-CMAS composite structure mentioned above, and will not be elaborated further here.
[0089] In some embodiments, the rare earth-modified gadolinium zirconate is ytterbium-modified gadolinium zirconate.
[0090] As one possible implementation method, the rare-earth modified gadolinium zirconate is ytterbium-modified gadolinium zirconate, and the chemical formula of ytterbium-modified gadolinium zirconate is (Gd 0.9 Yb 0.1 )2Zr2O7.
[0091] In some implementations, the femtosecond laser processing uses a laser with a center wavelength of 343 nm.
[0092] As one possible implementation, the average power of the femtosecond laser processing is 1W-20W; for example, it can be, but is not limited to, 1W, 2W, 4W, 6W, 8W, 10W, 12W, 14W, 16W, 18W, 20W, or any range between two of the above powers.
[0093] In some embodiments, the scanning speed of the femtosecond laser processing is 10 mm / s to 1000 mm / s; for example, it can be, but is not limited to, 10 mm / s, 100 mm / s, 200 mm / s, 300 mm / s, 400 mm / s, 500 mm / s, 600 mm / s, 700 mm / s, 800 mm / s, 900 mm / s, 1000 mm / s, or any range between two of the above speeds.
[0094] In some implementations, the number of repetitions of the femtosecond laser treatment is 1 to 20 times; for example, it can be, but is not limited to, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20 times or any range between any two of the above numbers.
[0095] When the laser center wavelength, average power, scanning speed, and number of repetitions of femtosecond laser processing are within the above-mentioned ranges, it is beneficial to prepare a lotus-leaf-like structure that meets the expected design and has the ability to increase the contact angle of molten CMAS.
[0096] In some implementations, the vacuum level in the main process chamber during magnetron sputtering deposition is 5 × 10⁻⁶. -6 Torr.
[0097] In some embodiments, the argon flow rate during magnetron sputtering deposition is 50 sccm-100 sccm; for example, it can be, but is not limited to, 50 sccm, 60 sccm, 70 sccm, 80 sccm, 90 sccm, 100 sccm or any range between two of the above argon flow rates.
[0098] In some embodiments, the target gun power during magnetron sputtering deposition is 50W-150W; for example, it can be, but is not limited to, 50W, 60W, 70W, 80W, 90W, 100W, 110W, 120W, 130W, 140W, 150W, or any range between two of the above target gun powers. Target gun power within the above range is advantageous for successfully fabricating magnesium oxide films of suitable thickness.
[0099] As one possible implementation, the ambient temperature during magnetron sputtering deposition is 100℃-300℃; for example, it can be, but is not limited to, 100℃, 150℃, 200℃, 250℃, 300℃ or any two of the above temperatures.
[0100] In some embodiments, the magnetron sputtering deposition time is 2 to 10 hours; for example, it can be, but is not limited to, 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, or any range between two of the above times. When the magnetron sputtering deposition time is within the above range, it is advantageous to prepare a magnesium oxide film layer on the surface of the processed structure.
[0101] It should be noted that when the process parameters of magnetron sputtering deposition are within the above range, it is beneficial to prepare a magnesium oxide film on the surface of the processed structure.
[0102] The material is ytterbium-modified gadolinium zirconate (GYbZ, (Gd) 0.9 Yb 0.1 Taking GYbZ ceramic blocks of 2Zr2O7 as an example, the preparation method of GYbZ ceramic blocks includes: mixing the original sprayed powder, zirconia balls and alcohol and then ball milling to break the powder and remove the glue to obtain GYbZ powder; pressing and sintering the GYbZ powder to prepare GYbZ ceramic blocks.
[0103] In some embodiments, the original spray powder comprises ZrO2, Gd2O3 and Yb2O3 in a molar ratio of 20:9:1.
[0104] As one possible implementation, the mass ratio of the original spray powder, zirconia balls, and alcohol is 1:3:3.
[0105] In some alternative implementations, the zirconia spheres have a diameter of 3 mm.
[0106] The technical solutions of this application will be described in detail below with reference to specific embodiments. It should be understood that these embodiments are only for illustrating this application and are not intended to limit the scope of this application. For experimental methods in the following embodiments where specific conditions are not specified, please refer to the guidelines given in this application first, or follow experimental manuals or conventional conditions in the field, or follow the conditions recommended by the manufacturer, or refer to experimental methods known in the field.
[0107] In the specific embodiments described below, the measurement parameters involving raw material components may have slight deviations within the weighing accuracy range unless otherwise specified. Temperature and time parameters are subject to acceptable deviations due to instrument testing accuracy or operational precision.
[0108] Unless otherwise specified, all raw materials in the following examples and comparative examples are commercially available or prepared using conventional methods.
[0109] I. Preparation of anti-CMAS composite structure
[0110] Example 1
[0111] S1. Ball milling: Preparation of GYbZ ((Gd 0.9 Yb 0.1The raw material for the Zr2O7 ceramic layer was GYbZ powder used in plasma spraying-physical vapor deposition (PS-PVD), with a molar ratio of ZrO2:Gd2O3:Yb2O3 of 20:9:1. 50 grams of the raw material powder was poured into a polytetrafluoroethylene ball mill jar, along with 150 grams of 3mm diameter zirconia balls and 150 grams of anhydrous ethanol. The mixture was prepared at a mass ratio of raw material powder:balls:ethanol = 1:3:3 and then ball-milled at 1000 rpm for 2 hours using a planetary ball mill. After milling, the suspension was poured into a beaker and dried in a 70℃ oven. The dried powder agglomerated and was crushed in an agate mortar. After sieving, the powder required for preparing the GYbZ ceramic layer was obtained.
[0112] S2. Pressing and sintering: Weigh 1.2g of GYbZ powder and place it into a stainless steel pressing mold with a diameter of 15mm. Hold the mold at 1.5t for 120 seconds. After demolding, a block with a diameter of 15mm and a thickness of 2mm is obtained. Place the block into a box furnace and sinter at an ambient temperature of 1600℃ for 10h to obtain a uniform GYbZ ceramic block. The density was measured to be 90.7%, which meets the requirements of subsequent experiments.
[0113] S3. Laser Processing: A femtosecond laser processing system is used to process the surface of the pressed and sintered GYbZ ceramic layer. In this embodiment, the laser center wavelength is 343 nm, the average power is 3 W, the scanning speed is 200 mm / s, and the number of repetitions is 8. The laser is generated by a laser source, transmitted through a transmission optical path, and perpendicularly incident on the sample surface. The scanning system scans and processes the surface of the ceramic block according to a preset scanning path, ultimately obtaining a ceramic layer with a specific lotus leaf-like structure.
[0114] S4. Magnetron Sputtering: A magnesium oxide film is deposited on the surface of the GYbZ ceramic layer with a lotus leaf-like structure formed by femtosecond laser processing. Magnesium oxide is used as the sputtering target, and the vacuum level in the main process chamber is reduced to 5 × 10⁻⁶. -6 Torr. Argon gas was introduced as the working gas at a flow rate of 80 sccm. The substrate temperature was set to 200 °C, and the RF power of the magnesium oxide target was set to 100 W. After the working gas pressure reached the preset conditions, the RF power supply was turned on for magnetron sputtering deposition, which lasted for 9 hours. After deposition, an anti-CMAS composite structure was obtained.
[0115] The three-dimensional laser confocal topography of the lotus leaf-like structure on the surface of the GYbZ ceramic layer obtained after S3 laser processing in Example 1 is shown in the figure below. Figure 2 As shown. By Figure 2 It can be seen that after laser processing, a lotus leaf-like structure is formed on the surface of the ceramic block.
[0116] The cross-sectional scanning electron microscope image of the anti-CMAS composite structure prepared in Example 1 is shown below. Figure 3 As shown. Figure 3 In the image, (a) is a cross-sectional scanning electron microscope image, and (b) and (c) are elemental distribution maps obtained by energy dispersive spectroscopy (EDS).
[0117] Comparative Example 1
[0118] The preparation method of Comparative Example 1 is similar to that of Example 1, except that after obtaining the GYbZ ceramic bulk material in Comparative Example 1, no further laser processing or magnetron sputtering was performed; all other aspects are the same. Comparative Example 1 is detailed below:
[0119] S1. Ball milling: Preparation of GYbZ ((Gd 0.9 Yb 0.1 The raw material for the Zr2O7 ceramic layer was GYbZ powder used in plasma spraying-physical vapor deposition (PS-PVD), with a molar ratio of ZrO2:Gd2O3:Yb2O3 of 20:9:1. 50 grams of the raw material powder was poured into a polytetrafluoroethylene ball mill jar, along with 150 grams of 3mm diameter zirconia balls and 150 grams of anhydrous ethanol. The mixture was prepared at a mass ratio of raw material powder:balls:ethanol = 1:3:3 and then ball-milled at 1000 rpm for 2 hours using a planetary ball mill. After milling, the suspension was poured into a beaker and dried in a 70℃ oven. The dried powder agglomerated and was crushed in an agate mortar. After sieving, the powder required for preparing the GYbZ ceramic layer was obtained.
[0120] S2. Pressing and sintering: Weigh 1.2g of GYbZ powder and place it into a stainless steel pressing mold with a diameter of 15mm. Hold the mold at 1.5t for 120 seconds. After demolding, a block with a diameter of 15mm and a thickness of 2mm is obtained. Place the block into a box furnace and sinter at an ambient temperature of 1600℃ for 10h to obtain a uniform GYbZ ceramic block. The density was measured to be 90.7%, which meets the requirements of subsequent experiments.
[0121] Comparative Example 2
[0122] The preparation method of Comparative Example 2 is similar to that of Example 1, except that after obtaining the GYbZ ceramic block in Comparative Example 2, only laser processing was performed, and magnetron sputtering was not performed; all other aspects are the same. Comparative Example 2 is detailed below:
[0123] S1. Ball milling: Preparation of GYbZ ((Gd 0.9 Yb 0.1The raw material for the Zr2O7 ceramic layer was GYbZ powder used in plasma spraying-physical vapor deposition (PS-PVD), with a molar ratio of ZrO2:Gd2O3:Yb2O3 of 20:9:1. 50 grams of the raw material powder was poured into a polytetrafluoroethylene ball mill jar, along with 150 grams of 3mm diameter zirconia balls and 150 grams of anhydrous ethanol. The mixture was prepared at a mass ratio of raw material powder:balls:ethanol = 1:3:3 and then ball-milled at 1000 rpm for 2 hours using a planetary ball mill. After milling, the suspension was poured into a beaker and dried in a 70℃ oven. The dried powder agglomerated and was crushed in an agate mortar. After sieving, the powder required for preparing the GYbZ ceramic layer was obtained.
[0124] S2. Pressing and sintering: Weigh 1.2g of GYbZ powder and place it into a stainless steel pressing mold with a diameter of 15mm. Hold the mold at 1.5tor for 120 seconds. After demolding, a block with a diameter of 15mm and a thickness of 2mm is obtained. Place the block into a box furnace and sinter at an ambient temperature of 1600℃ for 10h to obtain a uniform GYbZ ceramic block with a density of 90.7%.
[0125] S3. Laser Processing: A femtosecond laser processing system is used to process the surface of the pressed and sintered GYbZ ceramic layer. In this embodiment, the laser center wavelength is 343 nm, the average power is 3 W, the scanning speed is 200 mm / s, and the number of repetitions is 8. The laser is generated by a laser source, transmitted through a transmission optical path, and perpendicularly incident on the sample surface. The scanning system scans and processes the surface of the ceramic block according to a preset scanning path, ultimately obtaining a ceramic layer with a specific lotus leaf-like structure.
[0126] Comparative Example 3
[0127] The preparation method of Comparative Example 3 is similar to that of Example 1, except that after the GYbZ ceramic block was prepared in Comparative Example 3, it was only subjected to magnetron sputtering and not laser processing; everything else is the same.
[0128] S1. Ball milling: Preparation of GYbZ ((Gd 0.9 Yb 0.1The raw material for the Zr2O7 ceramic layer was GYbZ powder used in plasma spraying-physical vapor deposition (PS-PVD), with a molar ratio of ZrO2:Gd2O3:Yb2O3 of 20:9:1. 50 grams of the raw material powder was poured into a polytetrafluoroethylene ball mill jar, along with 150 grams of 3mm diameter zirconia balls and 150 grams of anhydrous ethanol. The mixture was prepared at a mass ratio of raw material powder:balls:ethanol = 1:3:3 and then ball-milled at 1000 rpm for 2 hours using a planetary ball mill. After milling, the suspension was poured into a beaker and dried in a 70℃ oven. The dried powder agglomerated and was crushed in an agate mortar. After sieving, the powder required for preparing the GYbZ ceramic layer was obtained.
[0129] S2. Pressing and sintering: Weigh 1.2g of GYbZ powder and place it into a stainless steel pressing mold with a diameter of 15mm. Hold the mold at 1.5tor for 120 seconds. After demolding, a block with a diameter of 15mm and a thickness of 2mm is obtained. Place the block into a box furnace and sinter at an ambient temperature of 1600℃ for 10h to obtain a uniform GYbZ ceramic block with a density of 90.7%.
[0130] S3. Magnetron sputtering: A magnesium oxide film is deposited on the surface of the GYbZ ceramic layer with a lotus leaf-like structure formed by femtosecond laser processing. Magnesium oxide is used as the sputtering target, and the vacuum level in the main process chamber is reduced to 5 × 10⁻⁶. -6 Torr. Argon gas was introduced as the working gas at a flow rate of 80 sccm. The substrate temperature was set to 200 °C, and the RF power of the magnesium oxide target was set to 100 W. After the working gas pressure reached the preset conditions, the RF power supply was turned on for magnetron sputtering deposition, which lasted for 9 hours. After deposition, an anti-CMAS composite structure was obtained.
[0131] II. Structural and Performance Testing
[0132] 1. Structural tests were performed on the products in Examples 1-5 and Comparative Examples 1-3, including the following aspects: the height and half-width at half-maximum (WHM) of the lotus leaf-like structure, the distance between the tops of adjacent lotus leaf-like structures, the density and thickness of the magnesium oxide film layer, and the thickness of the ceramic layer. The test method was as follows:
[0133] The sample to be tested was prepared in cross sections, and the cross-sectional morphology of the sample was observed using a scanning electron microscope (SEM). The SEM images were then quantitatively analyzed using ImageJ software to obtain data such as the height and width of the lotus leaf-like structure, the thickness of the magnesium oxide film, and the CMAS corrosion depth.
[0134] 2. The products obtained in Examples 1-5 and Comparative Examples 1-3 were subjected to CMAS etching. The test method was as follows:
[0135] (1) CMAS corrosion test
[0136] Preparation: Synthetic CMAS was ground and crushed to obtain CMAS powder with uniform particle size. The samples prepared in the above examples and comparative examples were placed horizontally, and CMAS powder was evenly spread on the surface of the samples, with a spreading amount of approximately 20 mg / cm³. 2 The corrosion temperature was 1250℃, and the time was 2 hours.
[0137] Observation: The sample was resin-mounted and the cross-section was polished sequentially using 400-grit, 800-grit, 1200-grit, and 2000-grit sandpaper and a polishing machine. Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) were used to observe the CMAS erosion area, the distribution of corrosion products, and the penetration depth of molten CMAS.
[0138] The corrosion results of Example 1 and Comparative Example 1 are as follows: Figure 4 As shown. By Figure 4 It can be seen that the corrosion penetration of Example 1 is reduced, demonstrating superior resistance to CMAS erosion.
[0139] (2) High-temperature molten CMAS contact angle test
[0140] Preparation: Pour the ground CMAS powder into a standard mold, press the powder firmly, and slowly demold to obtain a sample with a cylindrical CMAS block. Place the sample in a lifting furnace, set the temperature to 1250℃, and remove the sample after it cools with the furnace.
[0141] Observation: A high-speed camera was used to record the spreading behavior of molten CMAS on the sample surface under high temperature conditions, and the contact angle between molten CMAS and the sample surface was measured.
[0142] Surface melting CMAS contact angles of Example 1 and Comparative Example 1 are as follows: Figure 5 As shown. By Figure 5 It can be seen that after femtosecond laser processing and magnetron sputtering deposition of magnesium oxide film, the contact angle of molten CMAS on the sample surface increases.
[0143] The test results of the above embodiments and comparative examples are shown in Table 1.
[0144] Table 1
[0145]
[0146] In Table 1, " / " indicates that the result does not exist.
[0147] As can be seen from the comparison of the results of Example 1 and Comparative Examples 1-3 in Table 1, the anti-CMAS composite structure prepared in this application can effectively reduce the corrosion depth and increase the contact angle, and has excellent anti-CMAS corrosion effect.
[0148] Comparison of the results from Example 1 and Comparative Examples 2-3 shows that the lotus leaf-like structure and the magnesium oxide film work synergistically. The lotus leaf-like structure can initially regulate the wettability of the ceramic layer surface, while the magnesium oxide film, as the main physical barrier, can block the contact and penetration of CMAS. Together, they achieve a multi-layered long-term protective effect of "physical barrier (film) + interface strengthening (laser modification) + potential chemical barrier (reaction layer)". The synergistic protective effect of the lotus leaf-like structure and the magnesium oxide film overcomes the limited protective capability of a single protective method in the CMAS erosion environment, thereby improving the CMAS erosion resistance and high-temperature service stability of the thermal barrier coating and extending its service life.
[0149] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0150] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A thermal barrier coating for CMAS composite structures, characterized in that, Including an anti-CMAS composite structure, the anti-CMAS composite structure comprising: A ceramic layer, wherein the material of the ceramic layer comprises at least one of gadolinium zirconate and rare-earth modified gadolinium zirconate, and the surface of the ceramic layer has a lotus leaf-like structure; and, A magnesium oxide film layer covers the lotus leaf-like structure surface of the ceramic layer.
2. The anti-CMAS composite thermal barrier coating as described in claim 1, characterized in that, The height of the lotus leaf-like structure is 7μm-12μm.
3. The anti-CMAS composite thermal barrier coating as described in claim 1, characterized in that, The half-width at half-maximum (WHM) of the lotus-leaf-like structure is 4 μm-6 μm.
4. The anti-CMAS composite thermal barrier coating as described in claim 1, characterized in that, The surface of the ceramic layer has the lotus leaf-like structure, which is arranged in an array.
5. The anti-CMAS composite thermal barrier coating as described in claim 4, characterized in that, The distance between the tips of adjacent lotus leaf-like structures is 9μm-11μm.
6. The anti-CMAS composite thermal barrier coating as described in claim 1, characterized in that, Includes one or more of the following characteristics: (1) The thickness of the magnesium oxide film is 1μm-4μm; (2) The thickness of the ceramic layer is 100μm-400μm; (3) The thickness of the ceramic layer is 100μm-300μm; (4) The rare earth modified gadolinium zirconate is ytterbium modified gadolinium zirconate; (5) The rare earth-modified gadolinium zirconate is ytterbium-modified gadolinium zirconate, and the chemical formula of the ytterbium-modified gadolinium zirconate is (Gd 0.9 Yb 0.1 )2Zr2O7.
7. The anti-CMAS composite thermal barrier coating as described in any one of claims 1 to 6, characterized in that, The anti-CMAS composite thermal barrier coating also includes an adhesive layer, and the adhesive layer and the anti-CMAS composite structure are stacked sequentially.
8. A method for preparing a thermal barrier coating for CMAS composite structures, characterized in that, The anti-CMAS composite thermal barrier coating includes an anti-CMAS composite structure, and the preparation method includes the step of preparing the anti-CMAS composite structure, which includes: The surface of the ceramic layer is processed by femtosecond laser to form a lotus leaf-like micro / nano structure on the surface of the ceramic layer; wherein the material of the ceramic layer includes at least one of gadolinium zirconate and rare earth modified gadolinium zirconate; Magnesium oxide was used as the target material to perform magnetron sputtering deposition on the surface of a ceramic layer with a lotus leaf-like micro-nano structure, forming a magnesium oxide film on the surface of the lotus leaf-like micro-nano structure of the ceramic layer, thus obtaining an anti-CMAS composite structure.
9. The method for preparing the anti-CMAS composite thermal barrier coating as described in claim 8, characterized in that, Femtosecond laser processing includes at least one of the following conditions: (1) The center wavelength of the laser used in femtosecond laser processing is 343nm; (2) The average power of femtosecond laser processing is 1W-20W; (3) The scanning speed of femtosecond laser processing is 10mm / s-1000mm / s; (4) The number of repetitions of femtosecond laser treatment is 1 to 20 times.
10. The method for preparing the anti-CMAS composite thermal barrier coating as described in claim 8 or 9, characterized in that, Magnetron sputtering deposition includes at least one of the following conditions: (1) The vacuum level in the main process chamber during magnetron sputtering deposition is 5×10⁻⁶. -6 Torr; (2) The argon flow rate during magnetron sputtering deposition is 50 sccm-100 sccm; (3) The target gun power during magnetron sputtering deposition is 50W-150W; (4) The ambient temperature during magnetron sputtering deposition is 100℃-300℃; (5) The magnetron sputtering deposition time is 2 hours to 10 hours.